Coaching Clinic Basic Movements and Dominant Physical Conditions for Athletes at Gemilang Raya FC (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Basic movements and dominant physical conditions are often still a problem for soccer players in supporting the strategies and tactics of a coach in building attacks or in defense, especially at Football Club Gemilang Raya Kuningan. Some players still have shortcomings in carrying out correct and accurate basic movements and do not yet know the physical procedural requirements that a professional soccer player must possess. Based on the problems faced, the STKIP Muhammadiyah Kuningan Service Team carried out activities to overcome the problems faced by partners. Community service activities aim to improve the abilities and skills of Football Club Gemilang Raya Kuningan athletes in performing basic movements and knowing the dominant physical condition. The activity was carried out at the Gemilang Raya Kuningan Football Club and was attended by 20 players. The method used is a coaching clinic which consists of 2 sessions. The material provided consists of understanding basic movements and dominant physical conditions, practice on basic movements and dominant physical conditions. The results of the activity to the community showed an increase in the abilities and skills of Football Club Gemilang Raya Kuningan players regarding basic movements and dominant physical conditions.